Value–based self–regulation as a mechanism for development of social justice in pedagogical interaction - Кlochek, L. V. (Збірник наукових праць "Проблеми сучасної психології", 2018)
The article presents the results of the theoretical and empirical study of a teacher’s value-based self-regulation as a mechanism for development of social justice in pedagogical interaction. Psychological mechanisms are defined as methods of qualitative transformations of the teacher’s personality that affect the structure of his axiological sphere, activate the process of appearance and development of the personal formation of social justice. Value-based selfregulation acts as a psychological mechanism, which, in the conditions of pedagogical activity, launches the process of regulation of the actions by a teacher’s personality in relation to each student in accordance with generally accepted norms of justice in the educational environment. It is evidenced that the teacher’s regulation of his actions takes place not only taking into account the external attributes of pedagogical activities. According to them, a teacher adjusts the internal manifestations of his personality, critically evaluates his qualities and actions, correlates them with socially recognized values and norms, makes qualitative transformations in his axiological sphere. The empirical study of the mechanism of value-based self-regulation among teachers showed that it is developed to a greater extent among experienced teachers having a pedagogical experience of 21 years and above. This is manifested in the awareness of their own dominant values, among which social justice takes the lead and asserts the teacher in the belief to act justly in the interaction with students. In contrast, among young teachers whose professional experience does not exceed 5 years, the mechanism of social justice is developed the least, due to the lack of professional experience and it is displayed in underdeveloped skills of regulation of their manifestations in interaction with students in accordance with social and professional values.